Anatomia comparada em corações de Xenarthras Neotropicais - Souza, Wilson Viotto de (2024)
The superorder Xenarthra, which includes the orders Cingulata and Pilosa (the latter comprising the suborders Folivora and Vermilingua), belongs to the class Mammalia, subclass Theria, and infraclass Eutheria. With 32 living species distributed across four families in the Neotropical fauna, it plays a significant role in the biomass of Brazilian mammals, standing out as a successful evolutionary tree. The heart, essential for the cardiovascular system, is a pump of cardiac striated muscle. In most mammals, the heart assumes a conical shape and has its own irrigation system through the coronary arteries, ensuring vital blood supply to itsfunctions. This research adopted a dual approach, involving cardiac morphometry in specimens of Myrmecophaga tridactyla (n=48) and Tamandua tetradactyla (n=13), establishing comparative inferences. Simultaneously, an analysis of coronary irrigation was conducted on hearts belonging to the superorder Xenarthra (n=82). The means of the morphometric variables indicated that adult M. tridactyla had an average cardiac mass of 90.2 (±31.0) grams, while juveniles exhibited an average of 12.8 (±9.2) grams. For T. tetradactyla, the mean cardiac mass was 21.8 (±8.6) grams. Significant differences (p < 0.05) were observed both between sexes and between species, with M. tridactyla having a proportionally larger heart compared to T. tetradactyla. Additionally, male T. tetradactyla had significantly larger hearts than females. In the analysis of coronary irrigation, all coronary arteries and their branches were dissected and counted in three families (Dasypodidae; Myrmecophagidae; Bradypodidae). The right coronary artery (100%; n=82), originating from the right sinus of the aortic bulb, ran through the right coronary groove emitting atrial branches, ventricular branches, the right marginal branch, and the subsinuous interventricular branch. The left coronary sinus supplied, in most animals, the left coronary artery (90.2%; n=74), which divided into the paraconal interventricular branch and the circumflex branch. The balanced coronary pattern (92.3%; n=72) was the most common in the superorder Xenarthra, although different methodological approaches may indicate a right coronary pattern.